Study of [Formula omitted] decays at [Formula omitted] = 8 TeV with the ATLAS detector - Aad, G; Abbott, B; Abbott, D. C; Abeling, K; Abidi, S. H; Aboulhorma, A; Abramowicz, H (The European physical journal. C, Particles and fields, 2024)
This paper presents a study of [Formula omitted] decays with the ATLAS detector at the Large Hadron Collider. The analysis uses a proton-proton data sample corresponding to an integrated luminosity of 20.2 fb [Formula omitted] collected at a centre-of-mass energy [Formula omitted] = 8 TeV. Integrated fiducial cross-sections together with normalised differential fiducial cross-sections, sensitive to the kinematics of final-state QED radiation, are obtained. The results are found to be in agreement with state-of-the-art predictions for final-state QED radiation. First measurements of [Formula omitted] decays are also reported.